Molecular engineering of a π-conjugated polymer film of the azo dye Bismarck Brown Y - Teixeira, M. F.S. [UNESP]; Barsan, M. M.; Brett, C. M.A. (Royal Society of Chemistry (RSC), 2016)
The construction of molecular nanostructures with tunable topological structures is a challenge in molecular engineering. We report a novel organic π-conjugated chromophore obtained by the electropolymerization of Bismarck Brown Y (4,4′-[1,3-phenylenedi(E)-2,1-diazenediyl]di(1,3-benzenediamine)), with important potential applications in optical and electrochemical materials. The study comprises evidence regarding the redox transitions during the electropolymerization process by potential cycling and information regarding the physico-chemical properties of the polymerized film by UV-Vis spectroscopy, electrochemical impedance spectroscopy and scanning electron microscopy. The spectral study indicates a π-conjugated planar structure with predominance of the cis isomer. The polymer with diverse molecular conformation paves the way to fabricate molecular miniature devices with various desired functionalities.